Social cohesion and attitudinal changes toward migration: A longitudinal perspective amid the COVID-19 pandemic - Castillo, Juan Carlos; Bonhomme, Macarena; Miranda, Daniel; Iturra, Julio (Frontiers in Sociology, 2023)
The COVID-19 pandemic has impacted social interactions and coexistence around the globe in dimensions that go far beyond health issues. In the case of the Global South, the pandemic has developed along with growing South-South migratory movements, becoming another key factor that might reinforce social conflict in increasingly multicultural areas as migrants have historically served as ‘scapegoats’ for unexpected crises as a way to control and manage diversity. Chile is one of the main destination countries for migrants from the Latin American and Caribbean region, and where COVID-19 outbreaks in migrant housing have intensified discrimination. In such a context, there is a need for understanding how the pandemic has potentially changed the way nationals perceive migrant neighbors. Drawing on the national social cohesion panel survey study ELSOC (2016-2021, N= 2927) the aim is to analyze the changes in nationals’ attitudes towards migrants -related to dimensions of social cohesion- over the last years and their relation with individual status and territorial factors. We argue that migration is perceived as a growing threat to national identity and customs, to growing unemployment and to a convivial culture, endangering social cohesion. The results indicate that Chileans perceive Latin American and Caribbean migrants more negatively after the pandemic, particularly those respondents with lower educational levels and who live in increasingly multicultural neighborhoods with higher rates of migrant residents.